Crystal structure of cyclo-bis(μ4-2,2-diallylmalonato-κ6O1,O3:O3:O1′,O3′:O1′)tetrakis(triphenylphosphane-κP)tetrasilver(I) - Peter Frenzel; Alexander Jakob; Dieter Schaarschmidt; Tobias Rüffer; Heinrich Lang (Acta Crystallographica Section E, 2014)
In the tetranuclear molecule of the title compound, [Ag4(C9H10O4)2(C18H15P)4], the AgI ion is coordinated by one P and three O atoms in a considerably distorted tetrahedral environment. The two 2,2-diallylmalonate anions bridge four AgI ions in a μ4-(κ6O1,O3:O3:O1′,O3′:O1′) mode, setting up an Ag4O8P4 core (point group symmetry -4..) of corner-sharing tetrahedra. The shortest intramolecular Ag...Ag distance of 3.9510 (3) Å reveals that no direct d10...d10 interactions are present. Four weak intramolecular C—H...O hydrogen bonds are observed in the crystal structure of the title compound, which most likely stabilize the tetranuclear silver core.